Gabaergic and opioid receptors mediate the facilitation of NaCl intake induced by alpha(2)-adrenergic activation in the lateral parabrachial nucleus - Andrade, Carina Aparecida Fabrício de [UNESP]; Oliveira, Lisandra Brandino de; Andrade-Franzé, Gláucia Maria Fabrício de [UNESP]; Luca Junior, Laurival Antonio de [UNESP]; Colombari, Débora Simões de Almeida [UNESP]; Menani, José Vanderlei [UNESP] (Elsevier B.V., 2015)
Alpha(2)-adrenergic, gabaergic or opioidergic activation in the lateral parabrachial nucleus (LPBN) increases sodium intake. In the present study, we investigated the effects of single or combined blockade of opioidergic and gabaergic receptors in the LPBN on the increase of 0.3 M NaCl intake induced by alpha(2)-adrenoceptor activation in the LPBN. Male Holtzman rats (n = 5-9/group) with cannulas implanted bilaterally in the LPBN were treated with the diuretic furosemide (10 mg/kg b wt.) combined with low dose of the angiotensin converting enzyme inhibitor captopril (5 mg/kg b wt.) subcutaneously. Bilateral injections of moxonidine (alpha(2)-adrenergic/imidazoline receptor agonist, 0.5 nmol) into the LPBN increased furosemide + captopril-induced 0.3 M NaCl intake (25.8 +/- 1.4, vs. vehicle: 3.8 +/- 1.1 ml/60 min). The opioidergic receptor antagonist naloxone (100 nmol) or the GABA(A) receptor antagonist bicuculline (5 nmol) injected into the LPBN partially reduced the increase of 0.3 M NaCl intake produced by LPBN moxonidine (11.8 +/- 4.0 and 22.8 +/- 4.5, respectively, vs. vehicle+moxonidine: 31.6 +/- 4.0 ml/60 min, respectively). Similar to the treatment with each antagonist alone, the combined injections of naloxone (100 nmol) and bicuculline (5 nmol) into the LPBN also partially reduced moxonidine effects on 0.3 M NaCl intake (15.5 +/- 6.5 ml/60 min). The GABA(B) receptor antagonist saclofen (5 nmol) injected into the LPBN did not change the effects of moxonidine on 0.3 M NaCl intake (24.3 +/- 17.8 ml/120 min). These results suggest that the increase of 0.3 M NaCl intake by alpha(2)-adrenergic receptor activation in the LPBN is partially dependent on GABA(A) and opioid receptor activation in this area.
Keywords: Sodium appetite; Adrenergic; GABA; Opioid; Dehydration; Thirst